Comparative immunohistochemical characteristic of expression levels of Ki-67, p53, caspase 3 in non-invasive and invasive intestinal-type gastric adenocarcinoma - V. A. Tumanskiy; T. A. Khrystenko (Patologìâ)
Aim. Comparison analysis of expression levels of Ki-67, p53, and caspase 3 was performed between the tumor cells and the stromal cells of non-invasive intestinal-type gastric adenocarcinoma on the one hand and the tumor cells and the stromal cells of invasive intestinal-type gastric adenocarcinoma on the other hand.